Linking RNA biology to lncRNAs - Goff, Loyal A.; Rinn, John L. (Genome Research, 2015)
The regulatory potential of RNA has never ceased to amaze: from RNA catalysis, to RNA-mediated splicing, to RNA-based silencing of an entire chromosome during dosage compensation. More recently, thousands of long noncoding RNA (lncRNA) transcripts have been identified, the majority with unknown function. Thus, it is tempting to think that these lncRNAs represent a cadre of new factors that function through ribonucleic mechanisms. Some evidence points to several lncRNAs with tantalizing physiological contributions and thought-provoking molecular modalities. However, dissecting the RNA biology of lncRNAs has been difficult, and distinguishing the independent contributions of functional RNAs from underlying DNA elements, or the local act of transcription, is challenging. Here, we aim to survey the existing literature and highlight future approaches that will be needed to link the RNA-based biology and mechanisms of lncRNAs in vitro and in vivo.
10.1101/gr.191122.115